Eficiência energética e econômica da produção de leite bovino em explorações familiares no município de Pardinho, região de Botucatu- SP - Costa, Zoraide da Fonseca [UNESP]; Bueno, Osmar de Carvalho [UNESP] (EIA Energy in Agriculture, 2011)
The study aimed to analyze the energy and economic efficiency rate family farms producing milk in the county of Pardinho, Sao Paulo State. The criteria used to define producers in this study is that outlined by the Brazilian agricultural credit system FEAP (Fund Expansion of Agribusiness Paulista). Through primary data, obtained by verbal reports, the agroecosystem technical itineraries were re-established, detailing the process applied, machinery, implements, equipment, supplies and manual work. These were transformed into energy and economic units, which allowed determining the established connection between energy economics outputs and inputs. The hypothesis of this study is that the energetic expenditure may be coincidental with economic expenditures. The energetic and economic flows were analyzed, using a structure of expenditures, by type, source and form of gross energy, as well as the energetic point of view. Four producers were found to have different technical itineraries. Producers 1 and 2 achieved the highest energy and economic efficiency rates. The producer with the lowest efficiency rates was producer 4. The energy sources not renewable like chemical fertilizers were the most used reaching an average of 82.9% for the energy and 52.86% for the economic expenditures. When comparing energy and economic efficiency it is possible to verify that both forms of analysis are close, obtaining a broader idea about energy resources allocation.

O objetivo do presente trabalho foi analisar os índices de eficiência energética/econômica das explorações agropecuárias familiares, produtoras de leite no município de Pardinho-SP. Para definição dos produtores familiares estudados foram utilizados os critérios do sistema oficial de crédito rural FEAP (Fundo de Expansão do Agronegócio Paulista). Por intermédio de dados primários, obtidos por relatos orais, foram reconstituídos os itinerários técnicos do agroecossistema, detalhando as operações utilizadas, máquinas, implementos, equipamentos, insumos e mão-de-obra. Estes foram transformados em unidades energéticas e econômicas, que permitiram a determinação das relações estabelecidas entre “outputs” e “inputs” energéticos/econômicos. A hipótese que orienta este estudo é de que a relação energética pode ser coincidente com as relações econômicas. Buscou-se estudar os fluxos energéticos e econômicos, utilizando uma estrutura de dispêndios, por tipo, fonte e forma de energia bruta, tanto do ponto de vista econômico quanto energético. Foram encontrados quatro produtores com diferentes itinerários técnicos. Os produtores 1 e 2 foram os que obtiveram um maior índice de eficiência energética/econômica. O produtor que apresentou menor eficiência foi o produtor 4. As fontes de energia não renováveis na forma de fertilizantes químicos foram as que apresentaram maior participação, com uma média de 82,9% para os dispêndios energéticos, e 52,86% para os econômicos. Ao relacionar a eficiência energética/econômica pode-se verificar que as duas formas de analises são próximas, obtendo-se assim, uma idéia mais ampla da alocação dos recursos energéticos.
Energetic and economic analysis of the dairy cattle production in family explorations at pardinho county by Botucatu region
Keywords: Family agriculture; Dairy cattle; Sustainability; Agricultura familiar; Bovinocultura de leite; Sustentabilidade